The ketogenic diet for bodybuilders and physique athletes - Tzur, A.; Roberts, B. M. (Strength and Conditioning Journal, 2020)
In the past decades, the ketogenic diet has received scientific interest as a diet which may be beneficial for athletes. We summarize the ketogenic literature and give competitive bodybuilders and physique athletes advice on whether the diet and ketone supplements are suitable for off-season and in-season use. The diet is effective for fat loss and has a strong hunger-reducing effect. Current evidence suggests it is suboptimal for bulking and gaining lean mass. Upon starting the diet, negative side effects should be expected and prevented by increasing intake of electrolytes, fiber, and water. Exogenous ketones are currently not recommended.